The Role of Islamic Education in Shaping Disciplinary Culture and School Climate: Evidence from Bengkulu Province, Indonesia - Sumarto Sumarto; Emmi Kholilah Harahap (STAI Hubbulwathan Duri, 2025)
This study examines the role of Islamic education in shaping a culture of discipline and improving school climate in senior high schools in Bengkulu Province, Indonesia. The quantitative survey design included two groups of 300 students and 50 teachers from various senior high schools. For the student sample, there were 30 people and the teacher sample was 5 people. The sampling method used stratified random sampling. They were selected from public and private high schools. Data were collected using structured questionnaires and analyzed through one-way ANOVA to identify differences in school climate perceptions based on the level of Islamic education integration. The findings reveal a significant positive correlation between the integration of Islamic education and improvements in student behavior, as well as in teacher-student relationships. The one-way ANOVA results show statistically significant differences in school climate perceptions corresponding to varying levels of Islamic education integration. Schools with stronger implementation of Islamic values demonstrated a more disciplined culture and a more positive, orderly, and motivational environment. The study highlights how Islamic education contributes not only to fostering discipline but also to creating a peaceful and inspiring school climate. The integration of Islamic values encourages students and educators to view discipline as a fundamental aspect of religious practice, promoting time management, adherence to school rules, and mutual respect. Islamic education plays a vital role in cultivating discipline and enhancing the overall school climate in Bengkulu Province. Its integration supports educational success by aligning moral teachings with behavioral expectations, contributing to a harmonious and productive school environment.